Hukum Wakaf Tunai di Indonesia Dalam Pendekatan Maqashid Syari’ah - Shodiqul Amin (IAIN Langsa, 2020)
Issues regarding endowments are often directed towards endowments of high-value objects such as land, buildings, and so on. Along with the times, new perceptions about waqf have been created, not only focused on high-value objects, but penetrated the practice of donating cash. Cash waqf is a fund collected by the endowment manager through the issuance of cash waqf certificates purchased by the public. The focus of this research is how the law that applies to cash waqf in Indonesia is mainly seen from the Maqashid Shari'ah approach. Issues regarding endowments are often directed towards endowments of high-value objects such as land, buildings, and so on. Along with the times, new perceptions about waqf have been created, not only focused on high-value objects, but penetrated the practice of donating cash. Cash waqf is a fund collected by the endowment manager through the issuance of cash waqf certificates purchased by the public. The focus of this research is how the law that applies to cash waqf in Indonesia is mainly seen from the Maqashid Shari'ah approach.